Bluetongue’s New Frontier—Are Dogs at Risk? - Rita Payan-Carreira; Margarida Simões (Veterinary Sciences)
Bluetongue virus (BTV), traditionally considered a pathogen of ruminants, has recently been documented in dogs, challenging conventional understanding of its epidemiology. This narrative review synthesizes emerging evidence regarding BTV infections in domestic and wild carnivores, examining transmission dynamics, pathogenesis, clinical manifestations, and diagnostic challenges. Carnivores can become infected through vector transmission and oral ingestion of infected material. While some infected carnivores remain subclinical, others develop severe clinical manifestations including hemorrhagic syndromes. BTV infection in carnivores is likely underdiagnosed due to limited awareness, nonspecific clinical signs, and absence of established diagnostic protocols for non-ruminant species. The potential role of carnivores in BTV epidemiology remains largely unexplored, raising questions about their function as reservoirs or dead-end hosts. Additionally, carnivores may contribute to alternative transmission pathways and overwintering mechanisms that impact disease ecology. Current biosecurity frameworks and surveillance systems, primarily focused on ruminants, require expansion to incorporate carnivores in viral maintenance and transmission. This review identifies significant knowledge gaps regarding BTV in carnivores and proposes future research directions, including serological surveys, transmission studies, and investigation of viral tropism in carnivore tissues. A comprehensive One Health approach integrating diverse host species, vector ecology, human interference, and environmental factors is crucial for effective BTV control and impact mitigation on human, animals, and environment.